Enhancing Mathematics Education Through Collaborative Learning: A Study of Two Stay Two Stray (Ts-Ts) and Think-Pair-Share (TPS) Models within Realistic Mathematics Education - Sunandar, Dede (International Enterprise Integration Association, 2023)
This study evaluates the Two Stay Two Stray (Ts-Ts) and Think-Pair-Share (TPS) learning models in Realistic Mathematics Education (PMR) arithmetic learning activities. The study examines how collaborative pedagogical methods affect students' mathematical ability, problem-solving skills, and participation in varied educational environments. A quasi-experimental approach included various participant groups of varying grade levels and academic skills. To evaluate results, the research methodology included quantitative assessments, qualitative observations, questionnaires, interviews, and data analysis. After PMR used Ts-Ts and TPS models, pupils' mathematics understanding improved significantly. Quantitative studies showed improved test results, indicating student proficiency. Qualitative evaluations showed higher engagement, dynamic peer interactions, and deeper conceptual understanding during collaborative learning. Student questionnaires and educator interviews confirmed that these models promote communication, critical thinking, and math applications. TPS highlighted systematic individual contemplation and inclusive involvement, while Ts-Ts promoted vibrant group conversations. The results imply that the Ts-Ts and TPS models work together to promote collaborative learning and accommodate varied learning styles. Integrating these concepts into curriculum frameworks, promoting educator professional development, and pushing for inclusive mathematical education policy are recommended.